Validity of Ethnomathematics-Based Student Worksheets Using the Kepahiang Traditional House in Geometric Transformations for Mathematical Conceptual Understanding - Listri Maya Sari; Winda Ramadianti; Apriza Fitriani (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
Learning geometric transformations requires a strong conceptual understanding due to their abstract nature. One effort to enhance students’ conceptual understanding of mathematics is through the development of contextual and meaningful instructional materials that incorporate local culture. This study is a research and development (R&D) study employing the 4D model (Define, Design, Develop, and Disseminate) aimed at examining the validity of the developed Student Worksheets. The validation of the Student Worksheets was conducted by two experts in mathematics education who evaluated the aspects of content feasibility, media, and language and readability. The data were analyzed using descriptive quantitative methods with percentage scores to determine the level of validity of the Student Worksheets. The results showed that the developed Student Worksheets obtained a validity percentage of 93.75% for the content feasibility aspect (very valid), 80.77% for the media aspect (valid), and 87.50% for the language and readability aspect (very valid), with an overall average of 87.34%, which falls into the very valid category. Based on these results, the ethnomathematics-based Student Worksheets using the Kepahiang Traditional House context are considered feasible for use as supporting instructional materials in learning geometric transformations.